Perceptual asymmetries and handedness: a neglected link? - Marzoli, Daniele; Prete, Giulia; Tommasi, Luca (Frontiers in Psychology, 2014)
Healthy individuals tend to weigh in more the left than the right side of visual space in a variety of contexts, ranging from pseudoneglect to perceptual asymmetries for faces. Among the common explanations proposed for the attentional and perceptual advantages of the left visual field, a link with the prevalence of right-handedness in humans has never been suggested, although some evidence seems to converge in favor of a bias of spatial attention towards the region most likely coincident with another person’s right hand during a face-to-face interaction. Such a bias might imply an increased efficiency in monitoring both communicative and aggressive acts, the right limb being more used than the left in both types of behaviour. Although attentional and perceptual asymmetries could be linked to right-handedness at the level of phylogeny because of the evolutionarily advantage of directing attention towards the region where others’ dominant hand usually operates, it is also legitimate to question whether, at the ontogenetic level, frequent exposure to right-handed individuals may foster leftward biases. These views are discussed in the light of extant literature, and a number of tests are proposed in order to assess our hypotheses.